Creating a Live and Flexible Normative Dataset for Netball - Croft, Hayden; Spencer, Kirsten; Taurua, Noeline; Wilton, Emily (Frontiers in Sports and Active Living, 2021)
Previous research has identified large data and information sources which exist about netball performance and align with coaches’ discussion during games. Normative data provides context to measures across many disciplines including fitness testing, physical conditioning, and body composition. These data are normally presented in tables as representations of the population categorised for benchmarking. Normative data does not exist for benchmarking or contextualisation in netball, yet coaches and players use performance statistics. A systems design methodology was adopted for this study where a process for automating the organisation, normalisation, and contextualisation of netball performance data was developed. To maintain good ecological validity a case study utilised expert coach feedback on the understandability and usability of the visual representations of netball performance population data. This paper provides coaches with benchmarks for assessing the performances of players, across competition levels against player positions for performance indicators. It also provides insights to a performance analyst around how to present these benchmarks in an automated “real-time” reporting tool.